2019
DOI: 10.1039/c9lc00038k
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming transport limitations in miniaturized electrophoretic delivery devices

Abstract: Combining experimental and theoretical approach, we demonstrate practical solutions to limiting currents in capillary-based electrophoretic delivery devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…Although the source electrolyte was loaded with ASA, the ELISA quantification indicated that the delivered molecule was SA (Figure C). With capillary OEIPs, irregularities in substance delivery have been observed due to concentration polarization, which in turn causes electric field enhanced water dissociation at the ion channel inlet (in the source electrolyte) . This phenomenon is particularly intense at low concentrations of drugs and for relatively larger (low diffusion constant) molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the source electrolyte was loaded with ASA, the ELISA quantification indicated that the delivered molecule was SA (Figure C). With capillary OEIPs, irregularities in substance delivery have been observed due to concentration polarization, which in turn causes electric field enhanced water dissociation at the ion channel inlet (in the source electrolyte) . This phenomenon is particularly intense at low concentrations of drugs and for relatively larger (low diffusion constant) molecules.…”
Section: Resultsmentioning
confidence: 99%
“…After the polymerization, the capillary was cut into 20 desired device lengths (15 mm) by a fiber cleaver, and these were assembled directly onto heat shrink tubes/reservoirs. The capillary OEIP devices were immersed and stored in 1 × 10 −3 m KCl (aq) electrolyte before use to hydrate the polycatanion membrane …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a variety of alternative technologies, organic bioelectronics offer unique methods for the delivery of therapeutic substances and an ideal foundation for the treatment of various disorders, bridging the signalling gap between biology and technology. 19,20,36,37 State of the art bioelectronic technologies allow in vivo and in vitro recording of neural activity, monitoring and manipulating of neural pathways, use of chemicals naturally occurring in the non-disease state, immediate treatment by self-regulation, precise control of substance delivery, and minimization of adverse effects arising from disturbance of the biological microenvironment by diffusive delivery. 22,38 State of the art bioelectronic devices have been developed providing a fundamental understanding of communication between cells and with their environment.…”
Section: State Of the Art Bioelectronic Techniquesmentioning
confidence: 99%